Comparison on the Aerodynamic Coefficients Obtained from Three Different Size of Wind Tunnel Model on Baseline V Set at 45 Degree Sweep Tail Angle - Zulfazli Arief Bin Abd Latif, Mohamad; Effendy Mohd Nasir, Rizal; Aiman Bin Ahmad, Muhammad; Wisnoe, Wirachman; Kuntjoro, Wahyu; S. Ishak, I.; R S Saad, M. (International Journal of Engineering and Technology, 2018)
This paper analyzes the aerodynamic coefficients of a blended wing body, Baseline V which is equipped with 45Ëš sweep tail angle. Baseline V is one of the Universiti Teknologi MARA (UiTM) Shah Alam Flight Test Technology Centreâ€™s blended wing body designs that have unique configuration as it uses different NACA airfoil for its fuselage, body, wing root, midwing, wingtip, tail root, and tail tip. The intention of the comparison for three different size of wind tunnel model is to determine the similarity of the aerodynamics coefficients and the behaviour of the model itself. The wind tunnel experiments were conducted at three different wind tunnel locations: Universiti Teknologi Malaysia Skudai, UiTM Shah Alam and Universiti Pertahan Nasional Malaysia Kuala Lumpur, using 1:1 scale full model, 1:2 scale half model, and 2:7 scale half model, respectively. The data obtained are studied and plotted in term of lift coefficients, lift-to-drag ratio, and drag coefficients. The pitching angle for all experiments were varied between -10Ëš to +17Ëš. The blockage corrections have been applied to the data to obtain the actual performance of the aircraft. From the observations, the results show some similarity between those experiments, except for the lift-to-drag ratio of UPNMâ€™s data which are slightly higher compared to others.Â